Novel therapeutic targets in the treatment of obesity: a review - Alsharifi, Zainab Hafedh; Bash, Aymen A. (Pharmakeftiki, 2025)
Obesity is a chronic condition that increases the risk of both complications and mortality. The development of effective and safe entero-pancreatic peptide-based pharmacotherapies (such as those targeting ghrelin, leptin, peptide YY, and related molecules) requires a nuanced understanding of the gut–brain axis and its role in regulating appetite and body weight. This brief review places particular emphasis on novel incretin-based agents co-formulated with glucagon and neuropeptide Y, which have demonstrated weight-reduction outcomes approaching those of bariatric surgery, yet without the invasiveness of surgical intervention. In cases where obesity-related comorbidities (such as type 2 diabetes mellitus) are present, such substantial weight loss may contribute to clinical improvement, especially given that many of these agents exert independent effects on glycaemic control. Additionally, we herein evaluate the therapeutic potential of ghrelin inhibition via ghrelin-O-acyltransferase blockade, concluding that this approach does not yield meaningful effects on satiety, body weight, or caloric intake. Finally, we discuss emerging compounds currently under clinical investigation that may offer future avenues for obesity treatment.